MANAJEMEN PRAKTIKUM PEMBELAJARAN IPA - Tri Astuti Tri Astuti (Manajer Pendididikan, 2017)
The objective of research is to describe management science teaching practicum in junior high school Sidoharjo. The method of research is qualitative descriptive the subject of the  research are interview,observation and documentation. The result from research that in implementation of practical management science in junior high school Sidoharjo already running and adapted to the conditions of the school,so as to improve the quality of science teaching. Keyword: management, science, practicum